O crédito rural sob as perspectivas da posse da terra e da produtividade dos agricultores familiares - Dias, Thyena Karen Magalhães (2020)
Rural credit includes resources for funding, investment and marketing, being the main instrument of Brazilian agricultural policy. However, the absence of property rights over land is a controversial factor that, in turn, generates credit restrictions, since this is an asset used as collateral. Such restriction is markedly severe, particularly for the group of small farmers who, in Brazil, have the National Program for Strengthening Family Agriculture (PRONAF) as the only public policy aimed at them. In effect, this dissertation aims to answer two questions: what is the impact of family farmers' land tenure on access to rural credit? And what is the impact of rural credit on production in the Northeast? The work is structured in two chapters. The first chapter, entitled “The impact of family farmer land tenure on access to rural credit”, based on the microdata from the 2014 National Household Sample Survey, assessed the impact of land tenure by the so-called “Potentially Classified People as a Family Farmer ”(PPCAF) with respect to access to rural credit in Brazil. For this purpose, entropy balancing and Propensity Score Matching methods were used, and sensitivity was then analyzed in order to ascertain the robustness of the results in the face of the omitted variables. According to the results obtained, land tenure is unequivocal and positively related to rural credit, with emphasis on the Southeast region. In contrast, the results for the South and Center-West regions were not statistically significant. The second chapter, entitled “Rural credit and production in the semi-arid and nonsemi-arid regions of northeastern Brazil”, estimated the impact of rural credit for family farmers (Pronaf) on the production of temporary crops in the region, discriminating the impact in regions with a semi-arid climate. and not semi-arid. The database was obtained from the following sources: PAM, IBGE, BCB, MDA and INMET; in the period from 2012 to 2017, due to the availability of data, and these were analyzed using methods for panel data with fixed effects. The results showed that rural credit had a positive effect on production efficiency (gross value of production / planted area) during the analyzed period of time. However, this result proved to be valid only for the Northeast, in general, and for the municipalities that are in the semiarid region, since for the non-semiarid group the results were not statistically significant.